2012
DOI: 10.1515/cog-2012-0022
|View full text |Cite
|
Sign up to set email alerts
|

What do subject pronouns do in discourse? Cognitive, mechanical and constructional factors in variation

Abstract: In languages with variable subject expression, or “pro-drop” languages, when do speakers use subject pronouns? We address this question by investigating the linguistic conditioning of Spanish first-person singular pronoun yo in conversational data, testing hypotheses about speakers' choice of an expressed subject as factors in multivariate analysis. Our results indicate that, despite a widely held understanding of a contrastive role for subject pronouns, yo expression is primarily driven by cognitive, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 49 publications
7
60
0
8
Order By: Relevance
“…I based my choice of predictors on the findings of a multitude of previous SPE investigations (cf. Cameron 1992Cameron , 1993Cameron , 1995Enríquez 1984;Flores-Ferrán 2002Lastra & Martín Butragueño 2015;Orozco 2015;Otheguy, Zentella & Livert 2007;Torres Cacoullos & Travis 2010Travis 2005aTravis , 2005bTravis , 2007Travis & Torres Cacoullos 2012;among others). The four internal predictors analyzed here are (1) Verb class, (2) Prior subject's grammatical person and number, (3) Verbal tense, mood and aspect (TMA) of the verb, and (4) Grammatical person and number of the subject.…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
“…I based my choice of predictors on the findings of a multitude of previous SPE investigations (cf. Cameron 1992Cameron , 1993Cameron , 1995Enríquez 1984;Flores-Ferrán 2002Lastra & Martín Butragueño 2015;Orozco 2015;Otheguy, Zentella & Livert 2007;Torres Cacoullos & Travis 2010Travis 2005aTravis , 2005bTravis , 2007Travis & Torres Cacoullos 2012;among others). The four internal predictors analyzed here are (1) Verb class, (2) Prior subject's grammatical person and number, (3) Verbal tense, mood and aspect (TMA) of the verb, and (4) Grammatical person and number of the subject.…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
“…For example, Otheguy & Zentella (2012) report that their models capture some 18% of the variance (R 2 = 0.18). In part, this may be due to Zipfian biases and the skewing caused by high-frequency pronoun-verb collocations, which have only recently begun to attract the attention of researchers working on spe (e.g., Travis & Torres-Cacoullos 2012;Orozco 2015;Posio 2015). Also, earlier work has not reached a consensus on how to explain the effects of these predictors, which is mostly due to the fact that the common denominator of the results does not support any analysis completely (Travis 2007).…”
Section: The Phenomenonmentioning
confidence: 99%
“…In this regard, Travis & Torres-Cacoullos (2012) propose that the variation between the presence and the absence of subject personal pronouns (spps) involves the variable realization of the spp in an invariant <(spp) Verb> construction. However, this view presupposes that the default alternative is the presence of a spp, and that the deviation that only occurs under certain discourse conditions (cf.…”
Section: The Cognitive Constraints At Workmentioning
confidence: 99%
“…0 no está en la casa de granma. Studies applying a variationist methodology have shown that the variable expression of a subject is responsive to cognitive, semantic, and discourse factors (Shin 2014, Travis & Torres Cacoullos 2012. An overt subject is required under two conditions: 1) when it is focal, either because it is new information or the focus of contrast, and 2) when it is needed to identify its referent.…”
Section: Subject Realizationmentioning
confidence: 99%